Nominalizations in English Newspaper Writing - Smirnova, Daria (Univerzita Pardubice, 2023)
This bachelor thesis deals with the process of nominalization in three English newspapers. The aim of the thesis is to analyze the manifestations of nominal expressions in selected genres of journalistic style (news, views). The theoretical part in detail defines the formal means of nominalization, the systemic tendencies of English towards nominalization as well as the style-forming functions of this phenomenon (condensation, language economy, etc.) in media texts. The practical part includes the classification of the occurrences of nominalization according to established criteria, description of their frequency, and evaluation of the fulfillment of the main communication functions by nominalizations in newspaper writing.
Nominalizace v anglickém novinářském psaní
Keywords: nominalizace; derivace; konverze; verbonominální vazby; gerundium; příčestí přítomné; zpravodajský diskurz; BBC News; Guardian; Times; nominalization; derivation; conversion; middle verb; gerund; participle; newspaper writing; The BBC News; The Guardian; The Times